Pengaruh Influencer Dan Brand Ambassador Terhadap Purchase Intention Di Instagram Melalui Brand Equity Sebagai Variabel Intervening - Putri F O Bintang Mutiara; Rudy P.Tobing (Jurnal Bintang Manajemen, 2023)
This study used quantitative research methods with data collection techniques using questionnaires. The research sample consisted of Instagram users who had followed certain Influencers or Brand Ambassadors and had been exposed to their content. The collected data will be analyzed using path analysis to test the relationship between existing variables. The results of this study show an analysis that: (1) The influence of Influencers has a positive and significant effect on Brand Equity as evidenced by a calculated t value of 3.855 with a significance level of 0.00< 0.05 (probability value); (2) The influence of Brand Ambassadors has a positive and significant effect on Brand Equity as evidenced by a calculated t value of 3.990 with a significance level of 0.000 < 0.05 (probability value); (3) Influencers have a positive and significant effect on Purchase intention as evidenced by a calculated t value of 2.147 with a significance value of 0.033 < 0.05 (probability value); (4) Brand Ambassador has a positive relationship direction towards Purchase intention as evidenced by the calculated t value of 3.181 with a significance value of 0.002 < 0.05 (probability value); (5) Brand Equity has a positive relationship direction towards Purchase intention as evidenced by the calculated t-value results of 0.32 < 0.05 (probability value).